Financial Sector Assessment : Vietnam - World Bank (Washington, DC, 2014)
Vietnam has achieved remarkable progress since the start of its transition from a centrally planned economy in the mid-1980s. The Economic Renovation Policy announced in December 1986 marked the transition from a centrally planned economy to a mixed economy with greater reliance on markets and increased participation of private financial and non-financial institutions. These reforms contributed to an impressive performance in the last two decades, since 1990 the annual GDP growth has exceed 7 percent and per capita income has increased three-fold. This Financial Sector Assessment Program (FSAP) provides a broad set of policy recommendations that can be used to operationalize the SEDP and the banking restructuring program. The recommendations fall into three groups: (i) a plan to work out the large stock of existing NPLs; (ii) measures to ensure sound new flows of finance and prevent the accumulation of additional NPLs; and (iii) a set of policy steps designed to protect the financial sector during the envisaged reform period. For each group of measures, the plan identifies pre-conditions (first phase) and sub-sets of measures that needs to be implemented in the short run (second phase) as well as those that can be phased in over the medium term (third phase).